EFEKTIFITAS E-KATALOG PADA KEGIATAN PENGADAAN BARANG DAN JASA (PBJ) DALAM UPAYA PEMERINTAH MENCEGAH FRAUD - Sihaloho, Saut Wolker; Ariza, Dani; Munandar, Agus (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Government Procurement of Goods and Services (PBJ) through e-purchasing with e-catalog is expected to be as a more reliable method for PBJ officer, specifically for Commitment-making officer (PPK) and Procurement Officer (PP) due to the process has become faster and easier to choose between providers, as well as all transaction recorded in the LKPP e-catalog and therefore the process is transparent in nature. Procurement method with e-catalog expected can prevent fraud or human error. This study uses juridical normative approach by going through reference book, regulations, and related literature. Results of this research proof that Procurement of Government Goods and Services through e-katalog, has benefit in term of clarity, speed of the process and the simplicity, however in term of fraud resistance there is still loophole in the system. Through e-catalog prices can be see by anyone, selection process and also all transaction are recorded in the LKPP e-catalog therefore transparent in nature. However, price set in the LKPP e-catalogue are the highest in the government, therefore PP still has to negotiate the price.